2013
DOI: 10.1002/2013jc009116
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory model study of sediment transport sources and deposits in the Bohai Sea, Yellow Sea, and East China Sea

Abstract: A regional ocean circulation model (ROMS) is used to simulate the Chinese land‐derived sediment transport in the Bohai Sea, Yellow Sea, and East China Sea (BYECS). The model includes the effect of currents, tides, and waves on the sediment transport and is used to study the pathway and dynamic mechanisms of the fine‐grain sediment transport from the Huanghe River (Yellow River), the Old Huanghe Delta, and the Changjiang River (Yangtze River) in the BYECS. The seasonal variability of the sediment transport in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 64 publications
(101 reference statements)
12
92
0
1
Order By: Relevance
“…This decrease makes sea level change and wind-wave dynamics become increasingly important for the coastal development compared to fluviatile factors. At the same time the tide plays the dominant role in transporting sediments out of the sheltered embayment system to deeper shelf and the Yellow Sea ( Bian et al, 2013;Lu et al, 2013) . Numerical studies confirm the interpretation and estimation of Yang and Liu (2007) that along shelf sediment transport delivered by Yellow River formed clinoform deposits along the eastern tip of Shandong Peninsula in the Yellow Sea during the last 7000 years.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease makes sea level change and wind-wave dynamics become increasingly important for the coastal development compared to fluviatile factors. At the same time the tide plays the dominant role in transporting sediments out of the sheltered embayment system to deeper shelf and the Yellow Sea ( Bian et al, 2013;Lu et al, 2013) . Numerical studies confirm the interpretation and estimation of Yang and Liu (2007) that along shelf sediment transport delivered by Yellow River formed clinoform deposits along the eastern tip of Shandong Peninsula in the Yellow Sea during the last 7000 years.…”
Section: Introductionmentioning
confidence: 99%
“…There are two amphidromic points of M 2 ( Figure 11a) : one is near the mouth of the Yellow River at the south-western coast, and the other one is located offshore of Qinhuangdao at the northwestern coast. The model simulated maximum amplitude of the M 2 tide is about 110 cm in Liaodong Bay and 70 cm in Bohai Bay which are about 10% smaller than the M 2 amplitude calculated from TOPEX / Poseidon altimetry data and other model studies ( Bian et al, 2013;Huang et al, 1996;Pelling et al, 2013) .…”
Section: The Tidal-driven Regimementioning
confidence: 55%
“…In the surface layer, the Lagrangian residual currents form a clockwise flow in the Bohai Bay and the Liaodong Bay. In contrast, it flows north-eastwards into the Laizhou Bay and the central Bohai Sea with current speeds of 1~5 cm / s. In the bottom layer strong residual currents flow north-eastwards into the Liaodong Bay showing current speeds between 1~5 cm / s. Bian et al (2013) It should be noticed that the Bohai Sea has experienced rapid coastline changes recently due to natural developments of the Yellow River delta and large-scale anthropogenic land reclamation which substantially alters the tidal dynamics of this area. A numerical tidal model showed that the M 2 tidal amplitudes have changed by up to 0. 2 m over the last three decades due to the rapid coastal development ( Pelling et al, 2013 ) , and another numerical model showed that besides tidal amplitudes, the tidal energy flux is also affected by the land reclamation in the Bohai Sea ( Song et al, 2013) .…”
Section: The Tidal-driven Regimementioning
confidence: 98%
See 2 more Smart Citations